COMMUNICATION STRATEGIES IN SPEAKING SKILL OF EFL LEARNERS - Syamsudin Syamsudin (UIN Alauddin Makassar, 2015)
Abstract In EFL learning, among all the skills: listening, reading, and writing, speaking seems to be one of the most important skills. However, to master speaking is not an easy thing. And as a matter of fact, there are still many learners who have learned English for some years have not been able to speak fluently. Brown (2007) states that the difficulties the learners find in speaking are due to the fact that they have to focus on forms and function of the language. Further, Ellis (1994) also states that speaking has two sequential phases: planning and execution. Planning is done when speakers think of what utterance to produce to impact the listeners and execution is the realization of planning into words, phrases and sentences. To cope with the difficulties in speaking and to speak fluently, learners need to understand well about Communication Strategies. Thus, this paper tries to share ideas on the importance of the use of Communication Strategies to improve EFL learners’ speaking skill. It includes the nature of speaking, learners’ proficiency, communicative competence, communication strategies, and the research supports on Communication strategies. Strategi Komunikasi dalam Bercakap pada Pembelajar Bahasa Inggris sebagai Bahasa Asing. Dalam pembelajaran bahasa Inggris sebagai bahasa asing, diantara semua keterampilan menyimak, membaca, menulis, dan bercakap; kemampuan bercakap merupakan salah satu kemampuan yang terpenting. Namun demikian, bukan hal yang mudah untuk menguasai kemampuan ini. Beberapa fakta memperlihatkan bahwa banyak pembelajar bahasa Inggris yang telah belajar selama beberapa tahun namun belum dapat bercakap lancar. Brown (2007) menyatakan bahwa kesulitan yang ditemukan oleh pembelajar dalam bercakap adalah dimana mereka harus fokus pada bentuk dan fungsi bahasa. Lebih lanjut, Ellis (1994) juga mengemukakan bahwa terdapat dua langkah berkelanjutan dalam bercakap, yaitu perencanaan dan eksekusi. Perencanaan dilakukan saat pembicara berpikir ujaran apa yang harus diucapkan untuk memberikan dampak pada pendengar, dan eksekusi adalah realisasi perencanaan dalam kata-kata, frase dan kalimat. Untuk mengatasi kesulitan dalam bercakap lancar, pembelajar harus memahami tentang strategi komunikasi. Olehkarenanya, tulisan ini mencoba untuk berbagi ide tentang pentingnya penggunaan Strategi Komunikasi untuk meningkatkan keterampilan berbicara pembelajar bahasa Inggris sebagai bahasa asing. Strategi ini termasuk sifat berbicara, kemampuan peserta didik, kompetensi komunikatif, strategi komunikasi.